Nickel(0)-Promoted Carboxylation of Allenamides with Carbon Dioxide via a Nickelalactone Intermediate - Saito, Nozomi; Sugimura, Yasuyuki; Sato, Yoshihiro (Synlett, 2014)
Nickel(0)-promoted carboxylation of N-allenylamides (allenamides) with carbon dioxide proceeded via a nickelalactone intermediate to give β-amino acid derivatives. It was also found that the regioselectivity at the oxidative addition stage was strongly affected by the substituents on the allene part.
Keywords: nickel; allenamide; carbon dioxide; fixation; β-amino acid